A 5-microRNA signature identified from serum microRNA profiling predicts survival in patients with advanced stage non-small cell lung cancer. (14th November 2018) - Zhang, Yajie; Roth, Jack A; Yu, Hao; Ye, Yuanqing; Xie, Kunlin; Zhao, Hua; Chang, David W; Huang, Maosheng; Li, Hecheng; Qu, Jieming; Wu, Xifeng
Abstract: Circulating microRNAs (miRNAs) are potential biomarkers for cancer diagnosis, screening and prognosis. This study aimed to identify serum miRNAs as predictors of survival in patients with advanced non-small cell lung cancer (NSCLC). We profiled serum miRNAs in a pilot set of four patients with good survival (>24 months) and four patients with poor survival (<6 months). We selected 140 stably detectable miRNAs and 42 miRNAs reported in literature for further analysis. Expression of these 182 miRNAs was measured using high-throughput polymerase chain reaction assay, and their association with 3-year survival in the discovery ( n = 345) and validation ( n = 177) cohorts was assessed. Five serum miRNAs (miR-191, miR-28-3p, miR-145, miR-328 and miR-18a) were significantly associated with 3-year overall survival in both cohorts. A combined 5-miRNA risk score was created to assess the cumulative impact of these miRNAs on risk of death. Quartile analysis of the risk score showed significant association with 3-year death risk, with a 4.6-, 6.8- and 9.3-month reduction in median survival time for the second, third and fourth quartiles, respectively. Survival tree analysis also identified distinct risk groups with different 3-year survival durations. Data from The Cancer Genome Atlas revealed all five miRNAs were differentially expressed ( P < 0.0001) in paired tumor and normal tissues. Pathway analysis indicated that target genes of these five miRNAs were mainly enriched in inflammatory/immune response pathways and pathways implicated in resistance to chemoradiotherapy and/or targeted therapy. Our results suggested that the 5-miRNA signature could serve as a prognostic predictor in patients with advanced NSCLC. Abstract : This study involving global and targeted serum miRNA profiling of NSCLC patients identified five miRNAs associated with overall survival, which may serve as prognostic predictors in advanced NSCLC.